A Prospective Study on Autotransplantation of Mandibular Third Molars With Complete Root Formation. Issue 4 (December 2022) - Dhar, Shishir; Singh, Gaurav; Mishra, Madan; Gaur, Amit
Study Design: Autotransplantation, if possible, is a viable option for replacing a missing tooth when a donor tooth is available. The most typical tooth transplant is the transfer of a third molar to a first molar site. No immune reaction results from transplants of this nature. It restores the proprioceptive function and normal periodontal healing; thus, the patient can have a natural chewing feeling and natural biological response. Objective: This study aims to evaluate the prognosis of autotransplanted mandibular third molar and also to evaluate the cost effectiveness of the treatment performed when compared to the other treatment modalities for prosthetic rehabilitation. Methods: A prospective study was done in the Department of Oral & Maxillofacial Surgery, Sardar Patel Post Graduate Institute of Dental & Medical Sciences, Lucknow, UP, India, with over 20 patients to evaluate the prognosis of autotransplanted mandibular third molars with complete root formation after atraumatic extraction of first or second mandibular molar, which were randomly selected irrespective of race, sex, caste, and socio-economic status. Regular clinical and radiographical examinations were performed over a period of 1 year and the patients were assessed for pain, swelling, infection, dry socket, periodontal pocket depth, ankylosis, root resorption, tooth mobility, and level of buccal bone in relation to cementoenamel junction (CEJ). Results: Eighteen out of 20 transplants were successful; only 2 mandibular transplants were extracted because of abnormal horizontal and axial mobility and the reason of failure was attributed to fact that the roots of transplant were short and conical and there was lack of alveolar bone height at the recipient site in one patient, while root resorption was the reason for failure of transplant in the other patient. Conclusions: This study assessed the efficacy of autotransplantation of molars and the viability of the procedure to replace unrestorable molar teeth; it also supports the hypothesis that transplantation of a mandibular third molar for replacement of a lost or seriously damaged molar tooth could be a reasonable alternative.